2022
DOI: 10.1111/ele.13994
|View full text |Cite
|
Sign up to set email alerts
|

PERFICT: A Re‐imagined foundation for predictive ecology

Abstract: Making predictions from ecological models—and comparing them to data—offers a coherent approach to evaluate model quality, regardless of model complexity or modelling paradigm. To date, our ability to use predictions for developing, validating, updating, integrating and applying models across scientific disciplines while influencing management decisions, policies, and the public has been hampered by disparate perspectives on prediction and inadequately integrated approaches. We present an updated foundation fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…Our modelling efforts strive towards an open reusable approach, as described in McIntire et al (2022)…”
Section: Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…Our modelling efforts strive towards an open reusable approach, as described in McIntire et al (2022)…”
Section: Contextmentioning
confidence: 99%
“…We successfully adapted CBM to match the spatial scale of the management model, combined CBM with a fire model that uses the characteristics of the landscape to simulate the current disturbance regime until the landscape-level C stabilized, and standardized the software and information processing across all three models. This modelling system attempts to follow the reproducible, transparent and reusable approach as per McIntire et al (2022) rendering it readily adaptable to other study areas and available to iterative updating (Dietze et al 2018). Given that forest management and C models are jurisdiction-specific, our example is most easily reusable in BC, can be adapted to the rest of Canada, but could be adapted to jurisdictions with only the jurisdiction-specific information modified, rather than the whole workflow.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have also mapped multiple ESG dimensions using global datasets (Lèbre et al, 2019(Lèbre et al, , 2020Sonter et al, 2020). Continued progress on frameworks for modelling and predicting environmental and ecological risks with climate change require continued support (Lemieux and Scott 2005;Coristine and Kerr 2011;Dietze and Fox, 2018;McIntire and Chubaty, 2022) because many of the required datasets are either missing (e.g, quality of freshwater habitats and invertebrate biodiversity) or incomplete for large parts of Canada and globally (Brooks and Mittermeier, 2006;Coristine and Jacob, 2018). The United Nations Resource Management System has identified that these types of data gaps represent a major obstacle for managing and modelling the dynamic ESG that are essential for sustainable development (UNECE 2021b).…”
Section: Green Mining Starts With Green Explorationmentioning
confidence: 99%
“…dynamic and static models) will be key to overcoming barriers to transparency and reusability of predictive ecological models (Fer et al, 2021;Vedder et al, 2021). As a solution, McIntire et al (2022) proposed the PERFICT principles-making frequent Predictions and Evaluations of Reusable, Freely accessible, Interoperable models, built within Continuous workflows that are routinely Tested-to integrate all steps of a modelling exercise, including data preparation, geospatial processing, estimating model parameters, calibration, prediction, validation, visualisation and analysis of simulation results, and model code testing.…”
Section: Introductionmentioning
confidence: 99%